2019
DOI: 10.1002/brb3.1213
|View full text |Cite
|
Sign up to set email alerts
|

Is it worth turning a trigger into a joke? Humor as an emotion regulation strategy in remitted depression

Abstract: Aim Humor has long been considered as an effective emotion regulation strategy for people vulnerable to depression, but empirical evidence in this area is scarce. To address this issue, we investigated the emotional consequences of humor in remitted depressed patients and compared them with the effects of positive reappraisal and spontaneous emotion regulation. Methods Fifty‐five patients with remitted major depression took part in a laboratory computer experiment in wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 56 publications
4
13
0
2
Order By: Relevance
“…In line with the previous evidence of the beneficial impact of humor-based emotion regulation on remitted depression 23 , we expected that both stress-related humor and stress-unrelated humor would be effective in relation to all outcomes examined immediately and after a brief delay. We also presumed that, as demonstrated in previous clinical and non-clinical studies 23 , 38 , humor could impose some costs, such as requiring immense effort and compromising subsequent performance.…”
Section: Introductionsupporting
confidence: 63%
See 1 more Smart Citation
“…In line with the previous evidence of the beneficial impact of humor-based emotion regulation on remitted depression 23 , we expected that both stress-related humor and stress-unrelated humor would be effective in relation to all outcomes examined immediately and after a brief delay. We also presumed that, as demonstrated in previous clinical and non-clinical studies 23 , 38 , humor could impose some costs, such as requiring immense effort and compromising subsequent performance.…”
Section: Introductionsupporting
confidence: 63%
“…In addition, a research on short humorous interventions and perception of stressful events demonstrated that humor is a powerful tool to attenuate both psychological stress response and salivary cortisol levels 22 . Only one study has investigated the impact of humorous emotion regulation strategies in remitted depression; it demonstrated that the use of humor by previously depressed people to comment on a series of distressing scenes could alleviate their negative emotions, increase positive emotions, and enhance distance from adversity 23 . Additionally, humor-based regulation was found to be more effective than spontaneous regulation, but contrary to initial expectations, humor did not prevail over positive reappraisal.…”
Section: Introductionmentioning
confidence: 99%
“…Naturalistic observations, for example, have found that caregivers’ expressions of their own positive emotion, physical touch, and engagement sustained school-aged children’s expression of positive emotion (Bai et al, 2016 ). There is also an emerging focus on the link between humor and emotion regulation in both adults (Braniecka et al, 2019 ; Horn et al, 2019 ; Wu et al, 2021 ) and children and adolescents (Kuhlman et al, 2021 ; Mireault et al, 2015 ). A recent study found that infants aged five to seven months smiled more frequently, longer, and more quickly in response to an absurd event when caregivers provided cues that the event was humorous than when they provided neutral cues, suggesting caregivers can begin shaping their children’s understanding of humor very early on (Mireault et al, 2015 ).…”
Section: Future Directionsmentioning
confidence: 99%
“…Las personas que se exponen a él tienen una mayor tendencia a afectos positivos. La exposición a estímulos divertidos disminuye la experiencia de emociones negativas (Braniecka et al, 2019). Considerando el tipo de humor, se ha encontrado que el humor afiliativo y autoafirmativo se correlacionan negativamente con la soledad (MacDonald et al, 2020), con la ansiedad y la depresión; y positivamente con el optimismo (Menéndez-Aller et al, 2020).…”
Section: Funciones Del Humorunclassified